Synthesis and application of novel hyperbranched polymers - Goodwin, Sophie, R (2021)
In this thesis, a novel control method for the chain transfer polymerisation of di-functional monomers is presented, in which macromers, produced via catalytic chain transfer polymerisation, undergo β-scission to act as stoichiometric transfer agents for di-acrylate, -methacrylate and -styrenyl monomers. This versatile macromer control method enables the facile synthesis of hyperbranched (HB) polymers, which may be tailored for use as coatings in a wide variety of industrial and biological applications through suitable choice of monomer and macromer. In particular, the use of lauryl methacrylate macromers to control the polymerisation of divinyl benzene (DVB) (8:2 v/v LMA:DVB), facilitated the solubilisation of the HB DVB in hydrocarbyl engine oil through the incorporation of LMA fragments in the HB DVB structure. This HB DVB/LMA polymer was then demonstrated to readily form robust, protective films between metal contact surfaces under a wide range of temperatures, rolling speeds and lubrication regimes, which reduced friction and wear between the surfaces. Additionally, this synthesis method was found to be easily scalable, with the polymers demonstrating no significant difference in performance when synthesised at either 1 or 50mL scales. Thus, these HB polymers showed great promise as oil additives for prolonging engine life and improving engine efficiency, while the macromer control method was proven to the industrially viable. Meanwhile, when compared to catalytic control methods, macromeric control was found to give improved control over the polymerisation of the bio-active monomer tricyclodecanedimethanol diacrylate (TCDMDA), with greater consistency of polymerisation rate and architecture, and improved levels of functionality achieved due to the increased level of compatibility between the hydrophobic TCDMDA monomer and the macromer control agent. When butyl methacrylate macromers were used in a 2:1 v/v TCDMDA:BMA ratio, this enabled the synthesis of up to 50 mL of HB polymer which, when applied as a thin film coating to tissue culture plastic, was shown to support the growth of human pluripotent stem cells for up to 12 days. Finally, the use of thiolic control agents at high concentration (up to 65 mol%) was demonstrated to deliver improved yield of HB polymers, while enabling a similar ability to functionalise the HB polymers for a variety of applications, including as anti-fouling coatings and as a feedstock for two-photon polymerisation.